2010
DOI: 10.1038/nsmb.1786
|View full text |Cite
|
Sign up to set email alerts
|

Spinophilin directs protein phosphatase 1 specificity by blocking substrate binding sites

Abstract: The serine/threonine Protein Phosphatase 1 (PP1) dephosphorylates hundreds of key biological targets. PP1 associates with ≥200 regulatory proteins to form highly specific holoenzymes. These regulatory proteins target PP1 to its point of action within the cell and prime its enzymatic specificity for particular substrates. However, how they direct PP1’s specificity is not understood. Here we show that spinophilin, a neuronal PP1 regulator, is entirely unstructured in its unbound form and binds PP1, through a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
291
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(315 citation statements)
references
References 43 publications
15
291
1
4
Order By: Relevance
“…PP1-targeting subunits have been proposed to activate the phosphatase activity of PP1 or to target the phosphatase to its substrate (21). Because binding of an RVxF peptide does not appear to alter the conformation of PP1 (22)(23)(24), it seems likely that binding of a regulatory subunit containing an RVxF motif to PP1 is not sufficient to activate PP1 to dephosphorylate a specific substrate. However, in support of the scaffolding role of the PP1-targeting subunits, we previously showed that yeast eIF2γ contains a PP1-binding motif that enables recruitment of the phosphatase PP1/ GLC7 to its substrate eIF2α via the eIF2 complex (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PP1-targeting subunits have been proposed to activate the phosphatase activity of PP1 or to target the phosphatase to its substrate (21). Because binding of an RVxF peptide does not appear to alter the conformation of PP1 (22)(23)(24), it seems likely that binding of a regulatory subunit containing an RVxF motif to PP1 is not sufficient to activate PP1 to dephosphorylate a specific substrate. However, in support of the scaffolding role of the PP1-targeting subunits, we previously showed that yeast eIF2γ contains a PP1-binding motif that enables recruitment of the phosphatase PP1/ GLC7 to its substrate eIF2α via the eIF2 complex (25).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these subunits contain the conserved RVxF motif, which has been proposed either to allosterically affect the activity and/or substrate specificity of PP1 or to more simply target PP1 to its substrates (19)(20)(21)(22)(23). Notably, the latter idea is favored because binding of the RVxF motif has not been found to induce a conformational change in PP1 (22)(23)(24). To determine how GADD34 promotes the specific dephosphorylation of eIF2α by PP1, we established a yeast cell-based assay to monitor the dephosphorylation of human eIF2α mediated by the human GADD34-PP1 complex.…”
mentioning
confidence: 99%
“…L'« interactome » de la SPN comprend une trentaine de protéines parmi lesquelles des éléments du cytosquelette, des enzymes, des récep-teurs membranaires (GPCR et récep-teurs-canaux), des canaux ioniques, des facteurs d'échange de nucléotides guaniliques (GEF), des régulateurs de la signalisation des protéines G (RGS) et d'autres protéines comme le suppresseur de tumeur ARF (alternative reading frame, produit du locus INK4a/ARF). Il est ainsi progressivement apparu que la SPN n'était pas une simple protéine de régulation de certaines isoenzymes de la PP1 (comme l'alpha, PP1) mais une véritable protéine d'échafaudage dont les différents domaines permettent de former une plateforme de signalisation localisant la PP1c à proximité de ses substrats et lui conférant une spécifi-cité vis-à-vis de ceux-ci [4]. Bien que l'expression de la SPN soit ubiquitaire, les études se sont à ce jour surtout focalisées sur le rôle de la SPN dans les mécanismes de plasticité synaptique au niveau de l'hippocampe et du striatum [5].…”
Section: La Spinophiline Expression Tissulaire Et Partenairesunclassified
“…Spn is an unstructured protein in its unbound state that undergoes a folding transition upon interaction with PP1c into a single, stable conformation. The scaffolding protein binds to PP1c and blocks some potential substrate binding sites without altering its active site, then didacting substrate specificity of the enzyme (Ragusa et al, 2010). A further study showed that the PP1/Spn holoenzyme is dynamic in solution.…”
Section: -Spinophilin Structurementioning
confidence: 99%
“…GST-Spn fusion proteins containing the PP1c-binding domain potently inhibit PP1 enzymatic activity in vitro (Allen et al, 1997;Colbran et al, 2003). However, it was recently shown that instead of inhibiting PP1c directly, Spn regulated enzymatic activity by directing its substrate specificity (Ragusa et al, 2010). Spn can associate with the tyrosine phosphatase SHP-1 and the complex modulates platelet activation by sequestering RGS10 and RGS18.…”
Section: -The Spinophilin Interactomementioning
confidence: 99%